Dysregulation of ubiquitin homeostasis and β-catenin signaling promote spinal muscular atrophy - Wishart, Thomas M. (American Society for Clinical Investigation, 2014)
The autosomal recessive neurodegenerative disease spinal muscular atrophy (SMA) results from low levels of survival motor neuron (SMN) protein; however, it is unclear how reduced SMN promotes SMA development. Here, we determined that ubiquitin-dependent pathways regulate neuromuscular pathology in SMA. Using mouse models of SMA, we observed widespread perturbations in ubiquitin homeostasis, including reduced levels of ubiquitin-like modifier activating enzyme 1 (UBA1). SMN physically interacted with UBA1 in neurons, and disruption of Uba1 mRNA splicing was observed in the spinal cords of SMA mice exhibiting disease symptoms. Pharmacological or genetic suppression of UBA1 was sufficient to recapitulate an SMA-like neuromuscular pathology in zebrafish, suggesting that UBA1 directly contributes to disease pathogenesis. Dysregulation of UBA1 and subsequent ubiquitination pathways led to β-catenin accumulation, and pharmacological inhibition of β-catenin robustly ameliorated neuromuscular pathology in zebrafish, Drosophila, and mouse models of SMA. UBA1-associated disruption of β-catenin was restricted to the neuromuscular system in SMA mice; therefore, pharmacological inhibition of β-catenin in these animals failed to prevent systemic pathology in peripheral tissues and organs, indicating fundamental molecular differences between neuromuscular and systemic SMA pathology. Our data indicate that SMA-associated reduction of UBA1 contributes to neuromuscular pathogenesis through disruption of ubiquitin homeostasis and subsequent β-catenin signaling, highlighting ubiquitin homeostasis and β-catenin as potential therapeutic targets for SMA.